Abreviasi dalam Komunitas Penggemar Musikal Touken Ranbu di Media Sosial X: Kajian Morfologi - Mufidah, Nabila Sri (Vocational College of Diponegoro University, 2024)
Social media Twitter or currently called X limits the number of words that can be used in one tweet, especially for free users. This words limitation means that users have to use abbreviations. Abbreviation is also used in various communities, for example the musical Touken Ranbu Fans Community called 刀ミュ実況・乾燥語り場 (Toumyu Jikkyou/Kansou gatari ba) or Touken Ranbu Musical Live Commentary Forum. This research aims to find the forms of abbreviations used in the community, then classify and describe them. This research also aims to classify the forms of abbreviation that appear based on the type of 名詞 (meishi,